2015
DOI: 10.1002/anie.201504518
|View full text |Cite
|
Sign up to set email alerts
|

White‐Light Emission from an Integrated Upconversion Nanostructure: Toward Multicolor Displays Modulated by Laser Power

Abstract: The white backlight in displays is generated by optimizing the proportions of individual emitters with different wavelengths by variations in materials composition, phase, and structure. Color pixels usually result from the separation of white light or the excitation with multiwavelength or multipulse sources. However, it is a challenge to develop a material that comprises a single structure and emits over the full visible spectrum, but where the emission wavelengths can be controlled by a simple excitation so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
110
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(112 citation statements)
references
References 32 publications
1
110
0
1
Order By: Relevance
“…While the downconversion (DC) luminescence of various RE activators in La 2 O 2 SO 4 , Y 2 O 2 SO 4 , and Gd 2 O 2 SO 4 were investigated before, the upconversion (UC) property of RE in oxysulfate has only scarcely been studied up‐to‐date. UC phosphors play essential roles when converting longer wavelength radiation into shorter wavelength luminescence is needed in the multi‐faceted areas of solid‐state lasers, multi‐color display, drug delivery, fluorescent biomedical application, and wavelength converters for solar cells . Though RE halides (such as β‐NaYF 4 :Er/Yb) are currently the most efficient and widely used UC phosphors, a very recent study by Chen et al found that Er 3+ also shows promising UC luminescence under Yb 3+ sensitization in Y 2 O 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…While the downconversion (DC) luminescence of various RE activators in La 2 O 2 SO 4 , Y 2 O 2 SO 4 , and Gd 2 O 2 SO 4 were investigated before, the upconversion (UC) property of RE in oxysulfate has only scarcely been studied up‐to‐date. UC phosphors play essential roles when converting longer wavelength radiation into shorter wavelength luminescence is needed in the multi‐faceted areas of solid‐state lasers, multi‐color display, drug delivery, fluorescent biomedical application, and wavelength converters for solar cells . Though RE halides (such as β‐NaYF 4 :Er/Yb) are currently the most efficient and widely used UC phosphors, a very recent study by Chen et al found that Er 3+ also shows promising UC luminescence under Yb 3+ sensitization in Y 2 O 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Upconversion (UC) phosphor is drawing considerable attention due to its unique ability to convert longer wavelength radiation into shorter wavelength fluorescence [1, 2] and is finding wide applications in the fields of solid-state lasers [3], multi-color displays [4], drug delivery [5], fluorescent biological labels [6], wavelength converters for solar cells [7], and so forth. A UC phosphor is commonly formed by doping a host lattice with a sensitizer/activator pair, where the sensitizer is usually Yb 3+ and the activator is frequently being Ho 3+ , Er 3+ , or Tm 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Downshifting and quantum cutting belong to the conventional Stokes process where the emission energy is lower than the excitation energy. For example, multicolor emissions are expected for anti-counterfeiting, full-color display, and lighting, [23,24] red and near-infrared excitation and emissions are more suitable for biomedical treatment, [25,26] while ultraviolet, violet, and blue light are favored for photocatalysis and photovoltaic purposes. [3] The unique luminescent characteristics and energy transfer variety impart lanthanide materials great potentials in a wide range of fields, including but not limited to display and lighting, [4,5] laser, [6] information security, [7][8][9][10] sensing and detection, [11][12][13][14][15] biological imaging and therapy, [16][17][18] photocatalysis, and optoelectronic device.…”
Section: Introductionmentioning
confidence: 99%